A comprehensive overview of the burden, prevention, and therapeutic aspects of arboviral diseases in India - Himanshu Gupta; Pradip V. Barde; Mrigendra Pal Singh; Praveen K. Bharti; Nitika Nitika (Communications Medicine)
Abstract Outbreaks of arboviruses have become one of the major and consistent health burdens in India. With no effective vaccines or antivirals, it is challenging to control the exponential increase in cases of arboviral diseases. Accurate assessment of cases, timely and accurate diagnosis, treatment, tracking fatalities, surveillance of vectors, adopting integrated vector management policies, real-time genomic surveillance, and relating these to symptoms and tracking transmission are essential for keeping the emergence of arboviruses in check. This comprehensive review explores current literature and potential curative perspectives, focusing on major arboviruses, including dengue, chikungunya, Japanese encephalitis, Zika, Kyasanur forest disease, and Crimean-Congo haemorrhagic fever, and advancements in diagnosis, treatment protocols, supportive care, and the development of preventive measures. We aim to provide a thorough understanding of their epidemiology and impact in India, while identifying research and policy gaps that will enable policymakers to design effective strategies for managing the impact of arboviral diseases.